2017
DOI: 10.1016/j.eats.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Rotator Cuff Augmentation: Surgical Technique Using Bovine Collagen Bioinductive Implant

Abstract: Symptomatic partial-thickness rotator cuff tears and full-thickness tears with poor tissue quality often pose a dilemma for orthopaedic surgeons. Despite advances in repair techniques and fixation devices, retear rates remain high. Progression of partial-thickness tears has been noted to be over 50%, with remaining fibers seeing increased strain. Patch augmentation that induces a healing response while decreasing peak strain of adjacent tissue is becoming more popular among orthopaedic surgeons. Therefore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 5 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…Augmentation of the rotator cuff with autografts, allografts, xenografts, and synthetic materials provides surgeons with better surgical methods, especially for patients with large or massive RCTs, and can inhibit tendon retraction and reduce tension in injured shoulders. 1,4,9,20,24,32,42 Despite that the augment techniques are different, augmentation with fascial autografts has been suggested as a method for improving the healing process in RCTs. 40 Sano 35 built a fascia bridging graft rabbit model and found that newly formed insertion showed a histologic structure similar to that of a normal supraspinatus tendon insertion.…”
mentioning
confidence: 99%
“…Augmentation of the rotator cuff with autografts, allografts, xenografts, and synthetic materials provides surgeons with better surgical methods, especially for patients with large or massive RCTs, and can inhibit tendon retraction and reduce tension in injured shoulders. 1,4,9,20,24,32,42 Despite that the augment techniques are different, augmentation with fascial autografts has been suggested as a method for improving the healing process in RCTs. 40 Sano 35 built a fascia bridging graft rabbit model and found that newly formed insertion showed a histologic structure similar to that of a normal supraspinatus tendon insertion.…”
mentioning
confidence: 99%
“…59 The type I collagen bovine implant has gained recent popularity among orthopaedic surgeons as a viable option for biologic augmentation during rotator cuff repair due to its ease of insertion and its ability to induce new tissue formation and provide load sharing, decreasing the peak strain of the adjacent tissue and creating an environment more conducive to healing. 60 During RCR and implant placement, minimal cautery usage is important to preserve surrounding bursal tissue to assist healing as the medial bursa is responsible for blood supply to the tendon with either the marrow or bursa supplying the cells for healing.…”
Section: Utility Of Biologic Augmentationmentioning
confidence: 99%
“…As with any implant, there is a theoretical risk of an inflammatory or foreign body reaction. However, these risks have not been proven to be an issue in the literature [15][16].…”
Section: Introductionmentioning
confidence: 99%